Interpersonal Music Communication in the Serenade Bunga Bangsa Music Group in the Song Anjayeng Bawana - Atika Septiana Laksmi Atika (FAKULTAS DAKWAH UIN SALATIGA, 2024)
This research aims to determine the interpersonal musical communication of the Bunga Bangsa Serenade music group. This research uses qualitative methods with observation techniques and collects field data in stages. Observations were conducted at nine meetings at the DIY Culture Service, Yogyakarta Cultural Park, and the Ballroom of the Alana Palagan Hotel. After observation, a two-stage coding process was carried out. The first stage is to observe the communication between the performer and the musicians and choir during the practice process. Meanwhile, the second stage compiled categories consisting of communication, musical and non-musical vocabulary, and musical and non-musical gestures towards performers with musicians and choirs. The research results show that interpersonal musical communication can only be done during the practice process, whereas when the concert occurs, it relies only on musical gestures. This is due to the habit of using verbal rather than nonverbal communication during practice.